Catalytic Performance for Hydrocarbon Production from Syngas on the Promoted Co-Based Hybrid Catalysts; Influence of Pt Contents - Suk-Hwan Kang; Jae-Hong Ryu; Jin-Ho Kim; Hyo-Sik Kim; Hee Chul Yang; Dong Yong Chung (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
Fischer-Tropsch synthesis (FTS) reaction from syngas was investigated on the Pt-promoted cobalt-based hybrid catalysts prepared by co-precipitation method in a slurry of ZSM-5 (Si/Al=25). The hybrid catalysts were compared with each other for the different content of Pt as a promoter and are characterized using BET, XRD, H2-TPR and NH3-TPD. Their physicochemical properties were correlated with the activity and selectivity of the catalysts. As results, all hybrid catalysts show the C5-C9 yield (%) higher than that of Co-Al2O3/ZSM-5 catalyst. The Pt-promoted hybrid catalysts were found to be more promising towards production of the hydrocarbons of gasoline range and over C10.